Pengaruh Pengendalian Internal dan Kesesuaian Kompensasi terhadap Kecenderungan Kecurangan Akuntansi pada Perumda BPR Majalengka - Wulan Riyadi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
Accounting fraud related to corruption, an unusual action taken is to manipulate therecording, omission of documents, and mark ups that are detrimental to the country's financesor economy. Internal control is a representative of all activities within the organization thatmust be carried out to provide adequate confidence regarding the achievement of effectiveand efficient operational control objectives, the reliability of financial statements, andcompliance with the law. Compensation is often called an award and can be defined as a formof appreciation given to employees as a remuneration for the contribution they make to theorganization. This study aims to determine the effect of internal control and the suitability ofcompensation for trends in accounting fraud. The method used in this research is to usedescriptive and verification analysis. The population in this study were 36 people usingpuposive sampling techniques. Data collection technique is a survey with a questionnaire.Data instrument testing is done by using validity, reliability and data normality tests. Analysisof the data is the correlation of determination and hypothesis testing using the t test and Ftest. The data is processed using SPSS Version 21 and Microsoft Excel 2007. The resultsof this study indicate that internal control affects the tendency of accounting fraud. suitabilityof compensation affects the tendency of accounting fraud. Internal control and suitability ofcompensation affect the tendency of accounting fraud.